Splitting microresonator modes with the kerr-nonlinearity - Ghalanos, George N.; Silver, Jonathan M.; Bino, Leonardo Del; Moroney, Niall; Zhang, Shuangyou; Woodley, Michael T.M.; Svela, Andreas; Del'Haye, Pascal (Optics InfoBase Conference Papers, 2020)
We observe two-fold and three-fold splitting of optical modes in ultra-high-Q microresonators induced by the Kerr effect. This can be used for applications that require multiple resonances with precisely controlled offset.
CRIS-Team Scopus Importer:2024-12-16